2016
DOI: 10.1002/anie.201605239
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Frustrated Lewis Pair Reactivity with Selenium‐ and Boron‐Based Lewis Acids

Abstract: The activation of p-bonds in diynyl esters has been investigated by using soft and hardLewis acids.Inthe case of the soft selenium Lewis acid PhSeCl, sequential activation of the alkyne bonds leads initially to an isocoumarin (1 equiv PhSeCl) and then to atetracyclic conjugated structure with the isocoumarin subunit fused to ab enzoselenopyran (3 equiv PhSeCl). Conversely,t he reaction with the hard Lewis acidic borane B(C 6 F 5 ) 3 initiates acascade reaction to yield acomplex p-conjugated system containing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Alternatively,b orane activation of the alkyne followed by a1 ,2-trans-oxyboration reaction with subsequent proto-or carbodeboration could occur (pathway II,S cheme 6). Both pathways have been observed in other reactions with B(C 6 F 5 ) 3 .F or example,w eh ave previously noted the deprotection of Boc groups using catalytic amounts of B(C 6 F 5 ) 3 , which is reminiscent of pathway I, [20] while oxyboration pathway II has also been observed in studies by ourselves [20,21] and others [10b, 22] in the synthesis of oxazoles,d ioxaborinines, pyryliums,and lactones.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Alternatively,b orane activation of the alkyne followed by a1 ,2-trans-oxyboration reaction with subsequent proto-or carbodeboration could occur (pathway II,S cheme 6). Both pathways have been observed in other reactions with B(C 6 F 5 ) 3 .F or example,w eh ave previously noted the deprotection of Boc groups using catalytic amounts of B(C 6 F 5 ) 3 , which is reminiscent of pathway I, [20] while oxyboration pathway II has also been observed in studies by ourselves [20,21] and others [10b, 22] in the synthesis of oxazoles,d ioxaborinines, pyryliums,and lactones.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[104][105][106][107][108][109][110] Subsequent work by the groups of Melen, Stephan, Paradies, and Hashmi has demonstrated that strongly Lewis acidic boranes can be utilized to induce a wealth of intramolecular cyclization reactions involving propargyl esters 111,112 amides, 113 and related systems where an activated alkyne is attacked by an internal nucleophile. [114][115][116][117][118][119][120][121][122][123][124][125] Such reactions in many cases mirror transformations accessible typically via carbophillic Au or Pt catalysts. 103 An exemplary cyclization of a 1,5-enyne 115 is presented in Figure 8, which may be accessed via either boron-or gold-based catalysis.…”
Section: Alkynesmentioning
confidence: 99%
“…The different reaction conditions, solvents and catalysts used for constructions of 4-SÀ (Se, Te)-isochromenones 55 is summarized in Scheme 19. [50][51][52][53] Synthesis of 3-organoselanylchromone 57 was successfully achieved via iron(III) chloride and diorganyl diselenides 4 promoted intramolecular 6-endodig cyclization of alkynyl aryl ketone derivatives 56.…”
Section: Synthesis Of 4-organochalconylisochromenone and 3-organochalmentioning
confidence: 99%